Multivalued Nonlinear Weakly Picard Operators in Metric Spaces - Saiuparad, Sunisa; Muangchoo, Kanikar; Tangcharoen, Sukjit; Mee-on, Phannika; Ekvittayaniphon, Sakulbuth (Progress in Applied Science and Technology, 2022)
In this paper, the concept of -contraction was presented and a new ﬁxed-point theorem for such contractions would be established. We provide applications to prove that there is a ﬁxed point for cyclic mappings. We also received ﬁxed-point results for the weak contraction type mappings.